GENÓTIPOS DE FEIJÃO-CAUPI CULTIVADOS NA REGIÃO DO ECÓTONO CERRADO/PANTANAL - SANTOS, Carla Medianeira Giroletta; SILVA, Jeferson Antonio dos Santos; CAPRISTO, Denise Prevedel; CRISTALDO, Cleilsom Melgarejo; CORREA, Agenor Martinho (ANAIS DO ENIC, 2020)
-